KUALITAS KEPEMIMPINAN, DISIPLIN KERJA, DAN LINGKUNGAN KERJA SEBAGAI FAKTOR PENDUKUNG PENINGKATAN KINERJA KARYAWAN - Pramesthi, Riska Ayu; Sari, Rini Kartika (Relawan Jurnal Indonesia, 2023)
The quality of leadership greatly affects the work discipline and work environment of an employee in an organization. A leader is defined as a person's ability to be able to influence other people, through communication, either directly or indirectly, with the intention of moving these people so that they are willing to follow the leader's wishes with understanding, awareness and pleasure. The leadership role, no doubt, also contributes to a company. Work discipline is a management action to encourage members of the organization to meet the demands of these various provisions, in other words employee discipline is a form of training that seeks to improve and shape the knowledge, attitudes and behavior of employees so that these employees voluntarily try to work cooperatively with employees who others and improve work performance (Siagian, 2013: 305). The work environment is everything that exists around the employee and can affect the carrying out of the tasks assigned to him, for example by having air conditioning (AC), adequate lighting and directions from the leader. This study aims to determine whether the quality of leadership, work discipline, and work environment can improve employee performance. The research method used is a qualitative method with the type of literature study or Library Research, which examines literature books in accordance with the theories discussed especially in the scope of Human Resource Management (MSDM). The results of this study indicate that the quality of leadership, work discipline, and work environment can improve employee performance, if carried out correctly in human resource management in a company.